13 bankers the Wall Street takeover and the next financial meltdown - Johnson, Simon 1963-; Kwak, James (Pantheon Books, 2010)
Johnson and Kwak examine not only how Wall Street's ideology, wealth, and political power among policy makers in Washington led to the financial debacle of 2008, but also what the lessons learned portend for the future
Includes bibliographical references (p. [223]-278) and index
13 bankers -- Thomas Jefferson and the financial aristocracy -- Other people's oligarchs -- Wall Street rising : 1980-- -- "Greed is good" : the takeover -- The best deal ever -- Too big to fail -- The American oligarchy : six banks
Keywords: Prognose; Banks and banking / United States; Bank failures / United States; Finance / United States; Financial crises / United States; Bank; Bank failures -- United States; Banks and banking -- United States; Finance -- United States; Financial crises -- United States; Vorgeschichte; Finanzkrise; Macht; USA